1992
DOI: 10.1111/j.1365-2044.1992.tb02018.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two approaches to sciatic nerve block

Abstract: Summary This study compared the posterior and popliteal fossa approaches for sciatic nerve block. Patients scheduled to undergo foot surgery were allocated randomly into one of two groups: group A (n = 20) received sciatic nerve block via the posterior approach and group B (n = 20) received a block using the popliteal fossa approach. All blocks were performed with the aid of a peripheral nerve stimulator and alkalinised 0.5% bupivacaine with 1 in 200 000 adrenaline was injected in a dose of 2 mg.kg Nineteen of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 8 publications
2
25
1
Order By: Relevance
“…However, the procedure was significantly less painful with the popliteal approach. 39,40 While Kilpatrick et al 39 reported a better success rate with the transgluteal approach (95 vs 45% of patients; P < 0.01), Fuzier et al 40 found no difference between the two groups (94-98%).…”
Section: Approachesmentioning
confidence: 99%
“…However, the procedure was significantly less painful with the popliteal approach. 39,40 While Kilpatrick et al 39 reported a better success rate with the transgluteal approach (95 vs 45% of patients; P < 0.01), Fuzier et al 40 found no difference between the two groups (94-98%).…”
Section: Approachesmentioning
confidence: 99%
“…In the study by A. W. Kilpatrick et al, it is proved that the rate of the development of the sciatic nerve blockade performed with alkalinized 0.5% bupivacaine with epinephrine (1:200,000) does not depend on the approach (classic gluteal approach or popliteal approach) [5]. M. Taboada et al have found out that when the sciatic nerve is blocked with ropivacaine or mepivacaine sensory blocks develop faster when regional blockade of the sciatic nerve is performed in the proximal areas rather than in distal areas [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, comparisons with other studies remain difficult because of the lack of complete and detailed results. 2,3,14 C Co on nc cl lu us si io on n Sciatic nerve anesthesia using the novel lateral technique described appears to be a useful technique for distal lower limb surgery. Compared to the previously described peripelvic or popliteal methods, the present technique offers the advantages of the supine position for performing the block and catheter insertion with a high rate of homogeneous anesthesia and a low incidence of side effects.…”
Section: Figurementioning
confidence: 99%
“…We reviewed the sensitive and motor blocks reported with bupivacaine containing anesthetic solutions using different approaches, 2,3,6,14 to the sciatic nerve (Table II). Our results confirm the high incidence and rapid onset of blockade of both the proximal and the distal trunks of the sciatic nerve.…”
Section: Objectifmentioning
confidence: 99%
See 1 more Smart Citation